PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN SAMPAH SEBAGAI UPAYA PENANGANAN KAWASAN KUMUH DI KAWASAN PECANGAAN KABUPATEN JEPARA - Sri Subekti; Iwan Prayoga; Agus Sarwo Edy Sudrajat (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2020)
Increased urbanization and the increase in the number of housing areas or settlements that are less organized, accompanied by increasing slums. Slum settlement is defined as a residential area that is unfit for habitation with irregular building conditions, has a high level of building density, with the quality of buildings and facilities and infrastructure that do not meet the requirements. The problem of this research is the low coverage of solid waste services and the increasing volume of non-organic waste that is difficult to recycle and the level of public awareness about cleanliness is the main problem of waste management. The purpose of this research is to solve the problem of solid waste as an effort to prevent settlements from slums and to create a community that cares about waste management. The conclusion of this research is the need for regular waste transportation services to TPS / TPA so that the Pecangaan area becomes cleaner, the procurement of trash bins for each RT so that the waste can be well accommodated and the infrastructure for the process of transporting waste, socializing to the community at community meetings about the importance of waste management that is carried out in a sustainable manner, providing incentives for communities / groups / areas that are able to manage their waste properly as pilot areas, providing training to residents on waste management with the 3R concept (Reuse, Reduce, Recycle).